Rabindranath Tagore a biography - Kripalani, Krishna 1907-1993; Visva-Bharati. (New Delhi UBS Publishers' Distributors, 2008)
Biography of Rabindranath Tagore, 1861-1941, Bengali litterateur.
"First edition of the biography by Krishna Kripalani was published in 1962 by Oxford to commemorate the birth centenary of the Poet."--A note from the publisher.
"Reprint 2008."--Title page verso.
Includes bibliographical references (pages [547]-559) and index.
Keywords: Tagore, Rabindranath -- 1861-1941.; Authors, Bengali -- 19th century -- Biography; Authors, Bengali -- 20th century -- Biography